Mononucleotide A-repeats may Play a Regulatory Role in Endothermic Housekeeping Genes. (July 2022) - Pholtaisong, Jatuphol; Chaiyaratana, Nachol; Aporntewan, Chatchawit; Mutirangura, Apiwat
Background: Coding and non-coding short tandem repeats (STRs) facilitate a great diversity of phenotypic traits. The imbalance of mononucleotide A-repeats around transcription start sites (TSSs) was found in 3 mammals: H. sapiens, M. musculus, and R. norvegicus . Principal Findings: We found that the imbalance pattern originated in some vertebrates. A similar pattern was observed in mammals and birds, but not in amphibians and reptiles. We proposed that the enriched A-repeats upstream of TSSs is a novel hallmark of endotherms or warm-blooded animals. Gene ontology analysis indicates that the primary function of upstream A-repeats involves metabolism, cellular transportation, and sensory perception (smell and chemical stimulus) through housekeeping genes. Conclusions: Upstream A-repeats may play a regulatory role in the metabolic process of endothermic animals.